2021
DOI: 10.1038/s41398-021-01252-7
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing of the 5-HT2C receptor in the central nucleus of the amygdala is involved in resilience behavior

Abstract: Post-traumatic-stress-disorder (PTSD) is a stress-related condition that may develop after exposure to a severe trauma-event. One of the core brain areas that is considered to be a key regulatory region of PTSD is the amygdala. Specifically, the central amygdala (CeA) is involved in emotion processing and associative fear learning memory, two main circuits involved in PTSD. Long term dysregulation of trauma-related emotional processing may be caused by neuroadaptations that affect gene expression. The adenosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…There is significant evidence that the 5HT 2C receptor and its isoforms are responsible for the expression of various pathological phenotypes, which can be linked to differences in basal activity ( Kawahara et al, 2008 ; Morabito et al, 2010 ; Warhaftig et al, 2021 ). Since the orthosteric site remains unchanged across the isoforms, and our structural findings suggest that the differences in Gαq activation are due to the changes in interactions between the receptor and G protein mediated by ICL2, one could imagine that an isoform-selective allosteric modulator could be designed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is significant evidence that the 5HT 2C receptor and its isoforms are responsible for the expression of various pathological phenotypes, which can be linked to differences in basal activity ( Kawahara et al, 2008 ; Morabito et al, 2010 ; Warhaftig et al, 2021 ). Since the orthosteric site remains unchanged across the isoforms, and our structural findings suggest that the differences in Gαq activation are due to the changes in interactions between the receptor and G protein mediated by ICL2, one could imagine that an isoform-selective allosteric modulator could be designed.…”
Section: Discussionmentioning
confidence: 99%
“…Altering 5HT 2C RNA editing in vivo leads to diverse neuropathological outcomes reminiscent of Prader-Willi syndrome ( Morabito et al, 2010 ) and profound metabolic alterations ( Kawahara et al, 2008 ; Xie et al, 2021 ). Dysregulated 5HT 2C RNA editing has also been implicated in several neuropsychiatric disorders, including depression, substance abuse, and schizophrenia ( O’Neil and Emeson, 2012 ; Warhaftig et al, 2021 ; Zhu et al, 2012 ). Previous reports have suggested that highly edited isoforms VSV and VNV are found in particularly high levels in rat, mouse, and human brains ( Niswender et al, 1999 ; Zhu et al, 2012 ), while both the unedited (INI) and the less edited INV isoforms have been identified in the choroid plexus ( Niswender et al, 1999 , 2001 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cue and contextual fear conditioning, rats were placed in the fear-conditioning apparatus for 3 min (using predator scent method, previously described in an article by Gal Warhaftig et al [7], and then a 30-s tone (2.8 kHz, 65 dB) was delivered. At the last second of the tone, a 1 s shock (1.5 mA) was applied to the floor grid.…”
Section: Behavioral Procedures 421 Fear Conditioning Modelmentioning
confidence: 99%
“…The amygdala is part of the limbic system and is considered essential in the formation and storage of emotional memories [6,7]. It is hypothesized that in fear conditioning, the basolateral amygdala (BLA) supports the formation of conditioned fear memory and projects to neurons in the central nucleus (CeA) for the expression of conditioned fear responses [8,9].…”
Section: Introductionmentioning
confidence: 99%